2009
DOI: 10.1890/08-0115.1
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal in heterogeneous habitats: thresholds, spatial scales, and approximate rates of spread

Abstract: What is the effect of landscape heterogeneity on the spread rate of populations? Several spatially-explicit simulation models address this question for particular cases and find qualitative insights (e.g., extinction thresholds) but no quantitative relationships. We use a time-discrete analytic model and find general quantitative relationships for the invasion threshold, i.e., the minimal percentage of suitable habitat required for population spread. We investigate how, on the relevant spatial scales, this thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 107 publications
(149 citation statements)
references
References 42 publications
7
140
1
1
Order By: Relevance
“…As noted by several authors (VanKirk, 1995;Fahrig, 2002;Dewhirst and Lutscher, 2009), the scale of landscape heterogeneity can have significant effects on population spread rates. Following the procedure outlined in Section 4.5, we scale the spatial variable by the period of the landscape and introduce the dimensionless parameterp = l 1 l , the percentage of good habitat.…”
Section: A Periodic Landscape 641 Homogeneous Dispersalmentioning
confidence: 98%
See 4 more Smart Citations
“…As noted by several authors (VanKirk, 1995;Fahrig, 2002;Dewhirst and Lutscher, 2009), the scale of landscape heterogeneity can have significant effects on population spread rates. Following the procedure outlined in Section 4.5, we scale the spatial variable by the period of the landscape and introduce the dimensionless parameterp = l 1 l , the percentage of good habitat.…”
Section: A Periodic Landscape 641 Homogeneous Dispersalmentioning
confidence: 98%
“…Numerous studies have also found that population persistence in patchy landscapes is highly sensitive to the scale of dispersal relative to landscape heterogeneity (VanKirk, 1995;Fahrig, 2002;Dewhirst and Lutscher, 2009). Most importantly, we wish to consider the effect of individual movement behavior at the interface of two 4.…”
Section: Chapter 4 Analysis Of Integrodifference Equations: Populatiomentioning
confidence: 99%
See 3 more Smart Citations